effet de la propolis de Tigzirt sur les rats Wistar rendus diabétiques - Belhamiti, Mustapha (My University, 2016)
The objective of this study is the demonstration of the effect of propolis ethyl acetate extract (EAP) of Tigzrit (Tizi-Ouzou, Algeria) on some biochemical parameters in diabetic rats Wistar already injected by streptozotocin (STZ 60 mg / Kg ip). A total of 30 male Wistar rats, (average weight equal to 160 ± 18 g) were divided, into six groups (five animals each). Four groups received 50, 100, 200 mg / kg EAP or 50 mg / kg of quercetin orally for 90 days, and the fifth is used as negative control (T) and received only water and food ad libitum. The last groups served as positive control serves G1 (made diabetic without treatment). In the end of the experiment, blood samples were collected by cardiac puncture to measure parameters of homeostasis. The results indicated that the EAP at 200 mg / kg reduced blood sugar levels in diabetic rats (3.33 g / L). Glycated hemoglobin (HbA1C) was also reduced under the effect of propolis. The effect of propolis on blood glucose and A1C is dose-dependent. The weight of diabetic rats treated with propolis (200mg / kg) significantly increased compared to the untreated diabetic rats. On the other hand, the concentrations of creatinine and urea decreased suggesting an improvement in renal function; the lipid profile of diabetic rats had also improved. The serum AST and ALT were reduced in the treated diabetic rats, compared to untreated.
Keywords: Diabète; propolis; quercétine; streptozotocine; homéostasie.; Diabetes; Extract of propolis; streptozotocin; antidiabetic effects.